EFFICIENT READING - Lily Marliah (Jurnal Sosioteknologi, 2007)
Efficient Reading is very useful for readers especially for students of universities because most books in universities are still printed in English. However, many Indonesian students of universities could't cope with university textbooks written in English. The objective of the writing was to present the way of reading efficiently. The writing presented some factors to do efficient reading : i determining the purpose of your reading; ii choosing the right material; iii using the text effectively; iv skimming and scanning to get an adequate understanding. The writer suggests that we have to make reading as a habit to improve your reading speed and understanding.